(untitled) (Albayan Scientific Journal, 2023)
This research is concerned with studying the phenomena of rhythm and image in the poetry of Mr. Abu SeifMoqarabHadoth Al-Barasi. In the first part, it discussed the most prominent rhythmic phenomena in his poetry and phenomenon of repetition, alliteration and its significance. The researchers moved to the second part, which clarified the structure of the poetic image, which includes the simile and the allegorical image. The researchers relied on the descriptive analytical method in studying and analyzing the rhythm and image phenomena and their analysis. The most important results were represented on the poet’s choice of the classic rhythm style and his benefit from the tonal energies of repetition and the anagrams that were mentioned extensively in his poetry . Regarding to the second section, the poet relied heavily on the poetic image in shaping his literary vision to the world around him, and he harnessed all these stylistic energies to serve the religious, social and political issues he believed in.